THE INFLUENCE OF GREEN MARKETING MIX ON GREEN PURCHASE INTENTION IN USING ECO-FRIENDLY PRODUCTS - Yuary Farradia; Mora Mora; Indra Kusumawati; Wahyu Widodo (International Journal of Economy, Education and Entrepreneurship, 2021)
The purpose of this study was to determine and assess the impact of the green marketing mix on green purchase intentions when using environmentally friendly products (A Case Study on Stainless Steel Straws). The quantitative research approach used in this study was questionnaires on a Likert scale of 1-5. Purposive sampling is a non-probability sampling strategy used in the data collection technique. The participants in this study are students and/or members of the general public who live in Surakarta City and are looking to purchase stainless steel straws. A total of 112 people took part in this study. The research instrument testing, traditional assumption testing, model accuracy test, multiple regression analysis tests, and t-test were utilized to analyze the data in this study The validity and reliability of the instrument are being tested in this study. The software IBM SPSS Statistics 22 version was utilized as the data collection strategy. This study discovered that the location of a green space has no bearing on the likelihood of making a green purchase. The green product has a large impact on green buy intent, as does the green price, and the green advertising has a significant impact on green purchase intention